Art as Work: About the Professionalization and Professionalism of Artists with Visual Impairment in Mexico - Dubiel, Monika (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The subject of my interest is the artistic activity of persons with visual impairment (mainly actors and photographers, as well as writers and musicians) in Mexico. The main goal of the article is the reflection on the given activity understood as a professional work. The main research problem can be formulated as follows: : what or who decides that someone can be called a profesional artist. The article is based on the results of the qualitative inquiry that I conducted in this environment between 2019 and 2022. The research uses various ethnographical techniques with a special emphasis on interviews supplemented by participant and non-participant observations. The findings indicate that there are two main aspects for the discussed problem: salary and experience. Constructed in both mentioned areas the category of recognition turns out to be crucial for self defining or defining someone else as a professional artist. My considerations are embedded in the disability studies paradigm. They are also strongly rooted in the local Mexican context.